New Magnetic Polymer Nanocomposites on the Basis of Isotactic Polypropylene and Magnetite Nanoparticles for Adsorption of Ultrahigh Frequency Electromagnetic Waves. Issue 5 (24th March 2018) - Ramazanov, M. A.; Hajiyeva, F. V.; Maharramov, A. M.; Di Palma, Luca; Sannino, Diana; Takafuji, Makoto; Mammadov, H. M.; Hasanova, U. A.; Shirinova, H. A.; Bayramova, Z. A.
ABSTRACT: In this study, we report about the preparation of magnetic polymer nanocomposites on the basis of isotactic polypropylene and magnetite Fe3 O4 nanoparticles. The structure and composition of polymer nanocomposite materials have been studied by scanning electron microscopy, atomic force microscopy, and X-ray dispersive analysis. The magnetic properties of polymer nanocomposites based on PP+Fe3 O4 have been investigated. It is found that not significant adhesion and agglomeration of nanoparticles occur, by increasing the nanoparticle content in polymer matrix up to 40%, and therefore they act as single-domain nanoparticles. The samples of nanocomposites based on PP+Fe3 O4, with up to 40% content of Fe3 O4, exhibit superparamagnetic properties. It was also found out that the magnetic polymer nanocomposite material based on PP+Fe3 O4 is able to absorb ultrahigh frequency electromagnetic waves in the frequencies range from 0.1 to 30 GHz. The increase in Fe3 O4 concentration from 5 to 40% at the 400 µm thicknesses of the films leads to an increase in absorption of electromagnetic waves of high frequency from 15 to 22.7%. GRAPHICAL ABSTRACT: